Comment la sociologie trouve-t-elle son fait ? - Jacques Hamel (Recherches Sociologiques et Anthropologiques, 2021)
The present article seeks to know the fact, the social fact, at the origin of sociological knowledge. What is it? What is its “materiality”? How is it conceived to be the object of the study proper to sociology? Having considered the classical thesis according to which “reality” corresponds to a “social construction”, always changing, the text approaches the subject on a properly epistemological level by looking at the operations of the transmutation of the fact into a scientific object. An illustration is finally given to show that this transmutation is possible in sociology without that leading us to think that the fact is only a pure “social construction”, and thus without any other materiality, and consequently without it being relative in all respects.